Developing Management Model for Youth Basketball Clubs in Guangzhou City - Wang , Haoxian; Phucharoen, Thongchat (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: In recent years, Guangzhou Basketball Club has developed rapidly. However, at present, there are few studies on the current and future development goals, development evaluation, management mode, and long-term planning of Guangzhou Basketball Club, and the research depth is insufficient. Therefore, this paper will analyze the development and management model of youth basketball clubs in Guangzhou, and combine political, economic, and social factors to provide effective strategies and suggestions for the development of basketball clubs in Guangzhou. The main goal of this study is to construct a management model for the development of basketball clubs in Guangzhou. Materials and Methods: Literature review, expert interviews, and focus group questionnaires were used to ensure the authenticity and validity of the survey contents. Then, the development and management model of the basketball club was established and its effectiveness was verified. A total of 21 experts were interviewed in this study, and the experts were divided into three groups: the first group consisted of 5 experts to discuss and evaluate the development and management of youth basketball clubs in Guangzhou; The second group consisted of 9 experts to ensure input on the proposed POLC conceptual model; The third group consists of 7 senior experts who are responsible for evaluating and validating the developed POLC model. The POLC model is a management model that divides the management process into four basic functions: Planning, Organizing, Leading, and Controlling. Each function has its specific application process. Steps in developing the POLC model) research and discuss the management of the Guangzhou Youth Basketball Club; 2) evaluate and study the important elements of the POLC model and develop a POLC conceptual model; 3) develop a draft POLC model through focus group discussions to ensure expert input on the POLC conceptual model; 4) The POLC model is evaluated and validated by senior experts, and the POLC model is revised and finalized. Frequency, average statistics, and content analysis were used for data analysis. Result: Through the evaluation and verification of the POLC model for the development and management of Guangzhou Youth Basketball Clubs by experts, the four components of the model were finally determined: 1) The project management model includes six elements: government policy and support, market and demand, club strategy and business model, school and education, financial resources, challenges, and trends. 2) There are 5 factors in the organizational management model: organizational structure and system, human resources, marketing and promotion, risk management, and financial sustainability. 3) There are 7 factors in the leadership management model: professional development, innovation and culture, staffing and expertise, external factors, performance management, work-life balance, and employee engagement. 4) There are 5 factors of the control management model: quality assurance, performance measurement, financial control, risk management, competition, and development. Conclusion: In terms of the quality evaluation of the POLC model, senior experts have conducted a good evaluation and verification of the POLC model for the development and management of Guangzhou Youth Basketball Clubs, and believe that the model system is complete, clear and implementable.